Development and Validation of a Novel Clinical Scoring System (INDO-TOS) for Predicting Post-Operative Outcomes in Indonesian Patients Undergoing Tonsillectomy/Adenoidectomy - Oliva Azalia Putri; Moon Kaeun; Aprilia Sari (Sriwijaya Journal of Otorhinolaryngology, 2025)
Introduction: Tonsillectomy and adenoidectomy (T/A) are among the most common surgical procedures performed in Indonesia. While generally safe, post-operative complications can occur, impacting patient recovery and healthcare costs. Existing risk prediction models are often developed in Western populations and may not be directly applicable to the Indonesian context due to differences in genetics, healthcare access, and environmental factors. This study aimed to develop and validate a novel, culturally-tailored clinical scoring system (INDO-TOS) to predict post-operative outcomes in Indonesian children undergoing T/A. Methods: A multi-center, prospective observational study was conducted across seven major cities in Indonesia (Medan, Palembang, Jakarta, Surabaya, Bali, Makassar, and Samarinda). Patients aged 2-18 years undergoing T/A for any indication were enrolled. Pre-operative data, including demographics, medical history, physical examination findings, and laboratory results, were collected. Potential risk factors were identified based on a literature review and expert consensus. The primary outcome was the occurrence of any post-operative complication within 30 days, including hemorrhage, infection, respiratory distress, dehydration, and prolonged pain. A logistic regression model was used to identify independent predictors of complications in a derivation cohort. A scoring system was developed based on the regression coefficients. The INDO-TOS was then validated in a separate, independent validation cohort. Model performance was assessed using receiver operating characteristic (ROC) curve analysis, calibration plots, and the Hosmer-Lemeshow goodness-of-fit test. Results: A total of 1500 patients were enrolled (Derivation cohort: n=1000; Validation cohort: n=500). The overall complication rate was 12.5%. Multivariate analysis identified age <5 years (Odds Ratio [OR] = 1.8, 95% Confidence Interval [CI] 1.2-2.7), pre-existing comorbidities (OR = 2.5, 95% CI 1.6-3.9), history of recurrent acute tonsillitis (≥4 episodes/year) (OR = 1.9, 95% CI 1.3-2.8), high Mallampati score (III/IV) (OR = 2.1, 95% CI 1.4-3.2), and prolonged operative time (>60 minutes) (OR = 1.7, 95% CI 1.1-2.6) as significant independent predictors of post-operative complications. The INDO-TOS, incorporating these factors, demonstrated good discrimination in the derivation cohort (Area Under the Curve [AUC] = 0.78, 95% CI 0.74-0.82) and validation cohort (AUC = 0.75, 95% CI 0.70-0.80). Calibration was satisfactory in both cohorts. Conclusion: The INDO-TOS is a novel, validated clinical scoring system that effectively predicts post-operative complications in Indonesian children undergoing T/A. It utilizes readily available clinical information and can be easily implemented in diverse healthcare settings across Indonesia. The INDO-TOS can aid clinicians in identifying high-risk patients, optimizing pre-operative care, and potentially reducing post-operative morbidity.